The Effect of Price and Service Quality On Buying Interest In Three-Brother Gallon Water - Apriansyah, Roky; Hermanto, Hermanto; Ningsih, Fitria; Hairudin, Abdul; Afriaris, Said (Green Publisher Indonesia, 2022)
The study was conducted on the refillable water of three brothers. Consumers ' buying interest in three brothers' refillable water has decreased every year, this is due to the price offered is still less competitive with competitors who sell The same product and the quality of service that is felt is still not suitable by consumers, thus consumers move to other places. The research uses a quantitative approach with primary data. The number of samples is 100 people, random sampling with accidental sampling. The results showed that the price and quality of service simultaneously affected consumers ' buying interest in the refillable water of the three brothers, the price partially affected the consumers' buying interest in three brothers' refillable water and the quality of service partially affect consumers' buying interest in three brothers' refillable water.